Violencia y conflicto en Hannah Arendt y Étienne Balibar: apuntes para el caso colombiano (2020)
This text seeks to approach the understanding of conflict and violence in the work of Hannah Arendt and Etienne Balibar, to analyze some questions about the Colombian case. Its objective was to analyze how a new understanding of social and political conflict could modulate our understanding of the relationship between violence, the state and politics.